PIMT/TGS1: An evolving metabolic molecular switch with conserved methyl transferase activity. Issue 8 (August 2022) - Edwin, Rebecca Kristina; Challa, Nagalakshmi; Sharma, Rahul; Satyamoorthy, K.; Parsa, Kishore; Misra, Parimal
Highlights: PRIP-interacting protein with methyl transferase domain (PIMT) is a dual-acting protein-A post-transcriptional modifier and an RNA methyl transferase. PIMT functions as a link between HAT- and non-HAT-containing coactivator complexes. PIMT regulates hepatic gluconeogenesis and lipid metabolism in the skeletal muscle. Cardiac-specific PIMT –/– mice suffered from increased myocardial damage. PIMT controls post-transcriptional regulation of HIV-1 and human telomerase RNA biogenesis. Abstract : Transcriptional coactivators play a crucial role in regulating gene expression. PRIP interacting protein with methyl transferase domain (PIMT)/trimethyl guanosine synthase 1 (TGS1) is a co-activator interacting protein with an RNA methyl transferase domain. PIMT serves as a bridge between HAT and non-HAT coactivators and differentially modulates gene expression. Disruption of PIMT is embryonic lethal. PIMT regulates hepatic gluconeogenesis and TNF-α-induced insulin resistance in the skeletal muscle. As a methyl transferase, PIMT controls post-transcriptional regulation of HIV-1 and is essential for human telomerase RNA biogenesis. This review comprehensively describes the dual role of PIMT, which promises to be a putative target in metabolic disorders.